Complexity, technology and the future of transformative politics. Issue 2 (17th February 2020) - Wallgren, Thomas; Pratap, Vijay; Priya, Ritu
ABSTRACT: This paper argues that the 'open space' idea remains the key source of strength for the World Social Forum as a tool for transformative, liberatory politics. We suggest that this space can be seen as inhabited by two political identities formed on the basis of what we call the conventional left narrative on the one hand and the civilizational narrative on the other. We propose that WSF can continue to fulfil its mission well by serving as a forum where political and social activists and intellectuals can meet and learn from each other to overcome their current weaknesses. Key to such overcoming, we suggest, is that technology and complexity are politicized – a task which may be difficult but the avoidance of which may be irresponsible.